Evaluasi Kebijakan Revitalisasi Pasar Tradisional di Kota Surakarta - Nida, Mufna Mubdiatun (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
Traditional Market revitalization in Surakarta had been continued. This study aimed to evaluate the revitalization of traditional markets in Surakarta as a whole. The approach in this study isÂ Â mixed method, with data collection techniques such as interviews, questionnaires, field observation and survey agencies.Â The data analysis techniques used were qualitative and quantitative descriptive. The population in this study 2,261 people traders and some visitors were encountered in the field. Several findings in this study include: (1) Found the problems caused by an imbalance between the large building with an area of land 2) There is a change program execution drawings (shop drawings) due to conditions / circumstances found in the field 3) Output the program is not accordance with the objectives of the program 4) the physical construction market is more beneficial for market users (traders and visitors) rather than improving the management aspects of the market.